2012
DOI: 10.2514/1.b34299
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Different Cooled Tips in A High-Pressure Turbine Cascade

Abstract: The thermal performance of the three turbine tips was investigated. The results are presented in terms of heattransfer coefficient (h), cooling effectiveness (), net heat-flux reduction (NHFR), and heat load. The calculations were performed using a cooled flat tip, a cooled cavity tip, and a cooled suction-side squealer tip in a cascade at a tip gap of 1.6%C. The results were validated using experimental data where possible. For an uncooled flat tip, the fluid dynamics are dominated by flow separation at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Computational fluid dynamics (CFD) tools were found to be able to produce good predictions of the thermal performance of the tip leakage flow in a number of studies, both at subsonic conditions (e.g., Zhou et al [9]) and at transonic conditions (e.g., Zhang et al [18]). In the current study, the commercial code ANSYS FLUENT is used to solve steady Reynolds-averaged Navier-Stokes (RANS) equations.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
See 4 more Smart Citations
“…Computational fluid dynamics (CFD) tools were found to be able to produce good predictions of the thermal performance of the tip leakage flow in a number of studies, both at subsonic conditions (e.g., Zhou et al [9]) and at transonic conditions (e.g., Zhang et al [18]). In the current study, the commercial code ANSYS FLUENT is used to solve steady Reynolds-averaged Navier-Stokes (RANS) equations.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…The mesh of the flat tip used later in this paper has a tip Y of 3.7. The grid dependency study carried out at low speed (Zhou et al [9]) showed that the average heat transfer coefficient on the blade tip changes less than 4% when varying the tip Y from 2.8 to 7. This suggests that the prediction of the tip heat transfer coefficient is more sensitive to tip Y at highspeed conditions.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
See 3 more Smart Citations